APPLICATION OF CRIMINAL LAW OF PRISON IN CLASS II A PANCUR BATU PRISON BASED ON THE CRIMINAL JUSTICE SYSTEM - Gunawan Sandi Hutagaol; Hasdiana Juwita Bintang; Fitria Ramadhani Siregar (PT. Sinergi Legal Publisher, 2024)
The implementation of prison sentences in Indonesia is a law left over from the Dutch colonial era which is punitive and repressive. This characteristic was none other than influenced by the punishment teachings that were in effect at that time, namely retributive. According to retributive theory, punishment is given because the perpetrator of the crime must accept the punishment for the sake of the mistake. The purpose of this writing is to understand the historical and philosophical development of prison sentences in the criminal justice system, the main objective of implementing prison sentences in the criminal justice system, using normative legal research methods, namely research carried out by collecting and analyzing secondary data. This research is descriptive in nature, namely research by way of presentation which aims to obtain a complete picture (description) of the state of applicable laws and regulations linked to legal theories and the practice of implementing positive law regarding the protection of victims of sextortion crimes in cyberspace.